Ferrimagnetism of dilute Ising antiferromagnets - Timonin, P.N. (Физика низких температур, 2014)
It is shown that nearest-neighbor antiferromagnetic interactions of identical Ising spins on imbalanced bipartite lattice and imbalanced bipartite hierarchical fractal result in ferrimagnetic order instead of anti ferromagnetic one. On some crystal lattices dilute Ising antiferromagnets may also become ferrimagnets due to the imbalanced nature of the magnetic percolation cluster when it coexists with the percolation cluster of vacancies. As evidenced by the existing experiments on FepZn₁–pF₂, such ferrimagnetism is inherent property of bcc lattice so thermodynamics of these compounds at low p can be similar to that of antiferromagnet on imbalanced hierarchical fractal.